2021
DOI: 10.1155/2021/5574582
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Joint Damage in Osteoarthritis: Current Status and Future Directions

Abstract: Osteoarthritis (OA) is a disease of the whole joint organ, characterized by the loss of cartilage, and structural changes in bone including the formation of osteophytes, causing disability and loss of function. It is also associated with systemic mediators and low-grade inflammation. Currently, there is negligible/no availability of specific biomarkers that can be used to facilitate the diagnosis and treatment of OA. The most unmet clinical need is, however, related to the monitoring of disease progression ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 119 publications
0
60
0
Order By: Relevance
“…Furthermore, TNF-α blocks the chondrocyte synthesis of proteoglycans and type II collagen. IL-1β activates transcription factors via the MAPK and NF-κB signalling pathways to regulate inflammatory responses, resulting in the production of inflammatory mediators such as NO, PGE2, COX-2, and other catabolic factors that may accelerate cartilage degeneration [ 30 , 31 , 32 ]. Moreover, cytokines upregulate the gene expression of MMPs, which promotes the degradation of articular cartilage by breaking down proteoglycan, the main component of the ECM [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TNF-α blocks the chondrocyte synthesis of proteoglycans and type II collagen. IL-1β activates transcription factors via the MAPK and NF-κB signalling pathways to regulate inflammatory responses, resulting in the production of inflammatory mediators such as NO, PGE2, COX-2, and other catabolic factors that may accelerate cartilage degeneration [ 30 , 31 , 32 ]. Moreover, cytokines upregulate the gene expression of MMPs, which promotes the degradation of articular cartilage by breaking down proteoglycan, the main component of the ECM [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A deficiency across clinical trials that was found in the current review was a lack of reporting on biochemical biomarkers. Specific biomarkers related to metabolic changes due to KOA may be used for monitoring its progression, as well as for treatment development [ 35 , 36 ]. This is a topic that is gaining interest in KOA research, especially since current trials focus mostly on PROs and are unable to show metabolic changes of therapies on joint tissues.…”
Section: Discussionmentioning
confidence: 99%
“…This is a topic that is gaining interest in KOA research, especially since current trials focus mostly on PROs and are unable to show metabolic changes of therapies on joint tissues. However, there is currently no consensus on the collection of a specific set of biomarkers, as only a small number of biomarkers involved in the development of KOA have been identified so far [ 10 , 36 38 ]. For example, Yang et al (2015) showed that treatment with HA injections significantly reduced the concentration of cytokine interleukin-1β (IL-1β) in synovial fluid [ 39 ], while a study by Henrotin et al (2017) reported decreased levels of serum Coll2–1 [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cartilage oligomeric matrix protein is a component of cartilage tissue and synovial fluid. Since this protein is present only in this organ, its measurement in the blood can indicate the destruction or repair of the cartilage tissue [43]. HA as another marker, is one of the heavy molecules of glucosamine, which is a component of connective tissue.…”
Section: Measurement Of Biomarkersmentioning
confidence: 99%